WOMEN TRAFFICKING PERSPEKTIF PENDIDIKAN ISLAM - Noor Azida (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2023)
The phenomenon of women trafficking is a form of careless of human rights that still continues until now. The lack of education is a major factor in cases have claimed many victims of young Indonesian women. This has an impact on the lack of knowledge and the deterioration of the character of society. Therefor, education facilitates the acquisition of knowledge as well as values indispensable to. Islamic education is a transmission of values and knowledge based on Islamic spiritual values prioritizes the process of knowledge transformation which is accompanied by the development and strengthening of human character. Thus the horizon of thinking and public awareness getting widest and develop into a great power within individuals toward intelligence, noble character, and free from discrimination.